Reducing Lake Water Pollution Level With Media Filter Variations - Suhendra Suhendra (UIN Sulthan Thaha Saifuddin Jambi, Pusat Kajian Lingungan Hidup, 2023)
Most of the surface water such as rivers, lakes, or freshwater swamps were mostly polluted by human activities. This research analyzed the quality of surface lake water located in Gunugkidul Yogyakarta and the treatment of polluted water with three different filtration media variations based on the value obtained from the calculation of Water Quality Index (WQI) methodology. Based on the value obtained from water quality calculations using the Water Quality Index (WQI) system, the value of Winong Lake water ranges between 25.41-44.24 or is at a fair water quality level. Filter A reduces turbidity with an average of 26.98 NTU, but a significant reduction can be seen from the filtration results of filter B with an average value of 15.3 NTU. Furthermore, filter C with different media thicknesses has the potential to reduce turbidity although the results are not as significant as filter B with an average of 22.08 NTU. For color parameters, Filter A can reduce color with an average of 59 Pt-Co. filter B reduces the color by a further value with an average of 30 Pt-Co. Filter C produces quite good results, namely with an average value of 53 Pt-Co. In filter A, the detergent reduction reached an average of 0.06 mg/L, while in filter B, a very significant value was obtained, namely an average of 0.03 mg/L. For filter C, a slightly different value was obtained from filter A, namely with an average of 0.055 mg/L. The use of more active carbon media in filter B has a very big effect not only on reducing detergent but also on turbidity and color. Furthermore, the dose of chlorine chosen to remove pollutants and organic materials is 0.3 ml/100ml. From the research results, it was found that using more active carbon media in filter B was up to 77% effective in reducing all pollutant parameters in Winong Lake water.